2017
DOI: 10.1364/josaa.34.001085
|View full text |Cite
|
Sign up to set email alerts
|

Illuminant estimation in multispectral imaging

Abstract: With the advancement in sensor technology, the use of multispectral imaging is gaining wide popularity for computer vision applications. Multispectral imaging is used to achieve better discrimination between the radiance spectra, as compared to the color images. However, it is still sensitive to illumination changes. This study evaluates the potential evolution of illuminant estimation models from color to multispectral imaging. We first present a state of the art on computational color constancy and then exte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
3
1

Relationship

4
3

Authors

Journals

citations
Cited by 50 publications
(40 citation statements)
references
References 67 publications
1
39
0
Order By: Relevance
“…To overcome this limitation, the concept of multispectral constancy was recently proposed [38]. In this method, the estimation of illumination in multispectral images [39] is performed after the acquisition, and the effect of illumination is removed from the multispectral data. The spectral reconstruction system is trained/calibrated with the training data acquired with the same camera under a canonical illuminant.…”
Section: Discussionmentioning
confidence: 99%
“…To overcome this limitation, the concept of multispectral constancy was recently proposed [38]. In this method, the estimation of illumination in multispectral images [39] is performed after the acquisition, and the effect of illumination is removed from the multispectral data. The spectral reconstruction system is trained/calibrated with the training data acquired with the same camera under a canonical illuminant.…”
Section: Discussionmentioning
confidence: 99%
“…However, from a practical point of view, one reason for not employing such narrow band systems is that the acquisition time, complexity and cost of such system is high as compared to wide band systems [38]. Other reasons are the fact that the narrow band systems are not an optimal choice for illuminant estimation [16,17] and demosaicing (when multispectral filter array is used [39]). Wang et al [40] studied the influence of increase in number of bands and found that increasing the number of spectral bands cause reduction in performance of spectral reconstruction.…”
Section: Sensormentioning
confidence: 99%
“…Wang et al [40] studied the influence of increase in number of bands and found that increasing the number of spectral bands cause reduction in performance of spectral reconstruction. Also, the efficiency of illuminant estimation algorithms decreases when the number of spectral filters is increased [17]. In this work, we are limiting the experiments to linear systems and our aim is to investigate the concept of multispectral constancy 13 for a generalized multispectral imaging system.…”
Section: Sensormentioning
confidence: 99%
See 1 more Smart Citation
“…These algorithms are extensions of Max-RGB Algorithm [10] and the Gray-Edge Algorithm [11] [12]. The extension of these algorithms from color to spectral is discussed in detail in [9] [13]. Once the illuminant is estimated, then we propose to apply the SAT in form of a diagonal correction to the acquired data, so that it appears as if being taken under a canonical illuminant.…”
Section: Multispectral Constancy Through Satmentioning
confidence: 99%